THE PROBLEM OF ALCOHOL ABUSE IN THE FAMILY AND LOW ECONOMIC STATUS AS DETERMINANTS OF YOUTH RISK BEHAVIOR - Przybysz-Zaremba, Małgorzata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Objectives: The text presents research on the impact of alcohol problems occurring in the family on the manifestations of youth's risk behavior. Methods: The study was conducted among Polish youth attending junior and senior high schools, as well as their parents. In total, 150 people participated in the study. The study was conducted on the basis of the questionnaire addressed to parents, elaborated by us and the Social Maladjustment Scale developed by Lesław Pytka, addressed to young people. The aim of the study was to find out whether the problem of alcohol abuse observed in at least one parent/guardian and - resulting from that - low economic status of the family determine the risk behavior of young people. The study focused to these risky behaviors that are most often manifested by young people, i.e. physical aggression, verbal aggression, alcohol consumption, truancy and excessive sexual behavior. In order to perform statistical analysis, the IBM SPSS statistical program was used. Results: the study confirmed out suppositions that alcohol abuse in the family has a significant impact on the manifestations of adolescent risk behaviors, but this significance has not been fully confirmed for all variables. However, the low economic status of the family only determines selected risk behavior of young people.